แนวทางการพัฒนาภูมิทัศน์เวียงเจ็ดลิน เพื่อการอนุรักษ์และการท่องเที่ยว จังหวัดเชียงใหม่ - ศุภัชญา ปรัชญคุปต์ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
Wiang Jad Lin is one of the ancient communities in Chiang Mai. It is situated on the plain at the bottom of Doi Suthep. It was once settled by an indigenous community called "Lawa" or "Lua". In the period when they came to settle the area, the Lua dug a moat and built a dike to make the area more habitable and protect against enemy attacks. In the 7th Century, Wiang Jad Lin came under the influence of Buddhism as evidenced by the building of the Wat Koo Din Khao outside the town wall to the southwest, and from archaeological evidence such as ceramic Buddhist amulets dating back to the Haripunjaya Period. In 1411 AD, King Samfangan of the Mengrai Dynasty initiated restoration of Wiang Jad Lin to be used as a summer residence because of Doi Suthep’s shady and cool environment as well as Wiang Jad Lin’s clear and clean drinking water from its fountain springs. Over time, Wiang Jad Lin gradually decreased in importance. From the year 1967 up until the present, the growth of Chiang Mai city has expanded into the area with the establishment of official institutions, educational institutes, and residential communities. The findings of the study conducted in the Wiang Jad Lin area show that there are many problems relating to : the condition of the moat and the dike, the encroachment of residential development, the buildings of official and educational institutes adjacent to the archaeological sites resulting the increased deterioration and degradation of the moat and the dike and the archaeological sites. If such encroachment is allowed to continue, the moat and the dike and the archaeological sites will no longer be able to be seen by future generations. This thesis presents guidelines for developing and improving the landscapes of Wiang Jad Lin, focusing on the conservation of the archaeological sites, promoting local historical tourism and to creating a new public garden and green area for the city of Chiang Mai.